2015
DOI: 10.1007/s00421-015-3156-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between elastic properties of tendon structures and performance in long distance runners

Abstract: These results suggested that better long distance runners had stiffer tendon structures in the knee extensors and more compliant ones in the plantar flexors. These results implied that tendon structures in knee extensors and plantar flexors adapted to endurance running training and contributed to running performance of long distance runners separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
1
32
0
2
Order By: Relevance
“…Moreover, Fletcher et al [8] reported that, although stiffer plantar flexor tendon stiffness in women was correlated with greater running economy, no such significant correlation was observed in men, suggesting that plantar flexor tendon stiffness is insufficient for determining running economy. Furthermore, Kubo et al [18,21] reported that lower plantar flexor tendon stiffness was correlated with a faster personal best 5000-m race time, but running economy was not measured in this study. Thus, the relationship between plantar flexor tendon stiffness and running performance is unclear based on the findings in the previous studies [1,7,18,21].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, Fletcher et al [8] reported that, although stiffer plantar flexor tendon stiffness in women was correlated with greater running economy, no such significant correlation was observed in men, suggesting that plantar flexor tendon stiffness is insufficient for determining running economy. Furthermore, Kubo et al [18,21] reported that lower plantar flexor tendon stiffness was correlated with a faster personal best 5000-m race time, but running economy was not measured in this study. Thus, the relationship between plantar flexor tendon stiffness and running performance is unclear based on the findings in the previous studies [1,7,18,21].…”
Section: Introductionmentioning
confidence: 53%
“…Several previous studies examined the association between plantar flexor tendon stiffness and running performance [1,8,18,21]. Arampatzis et al [1] determined that greater plantar flexor tendon stiffness measured using ultrasonography is related to greater running economy.…”
Section: Introductionmentioning
confidence: 99%
“…Stiffness of tendons varies with age, sex, physical activity and fatigue (Kubo et al, 2001b, Kubo et al, 2001a, Kubo et al, 2001c, Reeves, 2006). Interestingly, different types of tendons modulate their stiffness to each other, for example in endurance running, tendons in the knee joints become stiffer and in planter joints softer to guarantee optimal running performance (Kubo et al, 2015). Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the mechanical properties of the muscle-tendon complex influenced performance and efficiency during stretch-shortening cycle exercises 8,9) . Therfore, it is possible that the stretchinginduced deficits in stretch-shortening cycle exercises are related to changes in the mechanical properties of the muscle-tendon complex.…”
Section: Introductionmentioning
confidence: 99%